Early life socioeconomic position and adult systemic inflammation: the role of gene regulation. (13th November 2019) - Carmeli, C; Kutalik, Z; Kelly-Irving, M; Delpierre, C; Bochud, M; Kivimaki, M; Vineis, P; Chadeau-Hyam, M; Dermitzakis, E; Stringhini, S
Abstract: Background: Adverse socioeconomic conditions in childhood affect systemic low-grade inflammation in adulthood. Studies in animals and humans suggest that socioeconomic conditions get under the skin from early life thus contributing to shape pro-inflammatory phenotypes. Although the existence of socioeconomic differences in gene regulation of the immune function have been described previously, no study has so far assessed the extent to which these differences actually explain socioeconomic variations in inflammatory markers. Methods: First, we ran 2-sample Mendelian Randomization (MR) methods to identify putative genes whose expression drives C-reactive protein (CRP) levels in blood. We used two databases with summary statistics of associations between single nucleotide polymorphisms and gene expression (eQTLGen, N = 31, 486 individuals) and CRP (CHARGE, N = 148, 164 individuals) in blood. We tested 10, 701 genes and retained those with FDR<0.05. Second, we used individual-participant data from a Swiss population-based study (SKIPOGH, N = 723) to estimate the proportion of the effect of paternal occupational position (SEP) on low-grade inflammation in adulthood (CRP>3mg/L) mediated by the selected genes. We estimated odds ratios and mediated proportions through counterfactual-based mediation models. Results: We identified 426 genes driving CRP levels (robust to unmeasured confounding thanks to MR). They jointly mediated the effect of low father's occupation on inflammation in adulthood for a proportion up to about 70% [95% confidence intervals (CI) 11-90%] and with an odds ratio of 1.53 [95% CI 1.05-2.15] compared to individuals with high paternal SEP. Analysis of the effects of life-course SEP trajectories (upward, downward and stable low from paternal to adult SEP) on gene regulation revealed trajectory dependent effects. Conclusions: We suggest that adverse childhood SEP affects systemic inflammation in adulthood through a long-lasting effect on gene regulation.